An estimate of meat production loss in native chicken in Bogor and its surrounding districts due to gasterointestinal helminthiasis - Simon He; Vici E.H.S. Susilowati; Endang Purwati; Risa Tiuria (Hemera Zoa, 1991)
Among 78 native chicken from Bogor and its surrounding districts, only  4 (5.1%) with mean dressing weights of 1250 ± 29 g were free from parasiric worms. The other 74 chicken found infected with nematodes [mean nematode numbers (mn) = 24]. Cestodes (mc = 45) and trematodes (mt = 7). Single parasite class infections of nematode (mn = 18) and of trematode (mt = 96) were each one sample (1.3% with mws 1250 and 1180 g, respectively); single parasite class infections of cestode (mc = 47) were 15 (19.2% wit mw = 1145 g). Total single parasite class infections were 17 (21.8%). Mixed nermatode (mn = 29) + castode (mc = 50) were 41 (52,6%; mw = 1056 g), nematode (mn = 4) + trematode (mt = 28) were 2 (2.6% mw = 1225 g) and cestode (mc = 44) + trematode (mt = 6 - were 2 (2,6%; ws = 975 g). Total two parasite class infections were 45 (57.7%). Mixed infections of nematode (mn - 45) + cestode (mc = 44) + trematode (mt = 27) were 12 (15,4%; mw = 1034 g).